Janamejaya’s Big Brother: New Light on the Mahābhārata’s Frame Story - Brodbeck, Simon (Religions of South Asia, 2008)
This article explores the story of Parikṣit in the Mahābhārata and suggests an interpretation whereby Parikṣit’s eldest son opted out of Parikṣit’s patriline, preferring that of his mother. This interpretation is supported by reference to various similar stories within the Mahābhārata and elsewhere. The article then suggests that several different Mahābhārata characters may be seen as parallel representations of Parikṣit’s eldest son. Finally, the article offers an explanation of the Mahābhārata’s oblique narrative strategy and reflects on the implications of these interpretations for the study of the text as a whole.